Membangun Loyalitas Melalui Realisasi Pembelian Analisis Ekuitas Merek dan Kualitas Pelayanan - Djumarno; Jubaedah; Khilyatin Ikhsani; Agung Hudaya (Jurnal Informatika Ekonomi Bisnis, 2023)
Economic recovery since the Covid-19 pandemic must be carried out, the MSME sector has become the focus of researchers in research. Because MSMEs do not require large capital to start a business, it will be easier for people to start. South Jakarta is a good market share for MSMEs, apart from being densely populated, culinary consumption has great potential. Knowledge of marketing strategies makes MSMEs have to compete fiercely, brand equity and service quality are fundamental in how they make customers buy their products again, which has implications for customer loyalty. This research will be oriented towards the development of MSMEs in the South Jakarta area, in collaboration with the National Development University (UPN). TKT in this research is oriented towards the use of information technology that is developing in society, in this case the use of online must be emphasized by MSME players to increase knowledge that will support their business. Researchers will ensure that MSME players will utilize technology to increase customer loyalty in their restaurants. 105 respondents will be the sample in the research which will then be processed using statistical applications with Smart PLS with the SEM method. The results show that high service quality contributes to customer satisfaction, which in turn has a positive effect on customer loyalty.